1990
DOI: 10.1055/s-2007-1013991
|View full text |Cite
|
Sign up to set email alerts
|

The Hydatid Cyst of the Lung in Children and Results of Surgical Treatment

Abstract: Between 1976 and 1986 one hundred and ten children with pulmonary hydatid disease were treated surgically. Sixty five of the patients were males and 45 were females. We diagnosed hydatid cyst in 36 cases submitted in our clinic with hemoptysis. Thirty of the patients had cough, 16 had chest pain and dyspnea, 12 had purulent sputum and 8 cases had fever and anaphylactic phenomena. In most of the patients hydatid cysts were localised in the right lung. However, they had affinity for the lower lobes of both lungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
2
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 0 publications
6
24
2
1
Order By: Relevance
“…Singh S et al, [4] have reported a 10-year-old child with recurrent hemoptysis and a bout of massive hemoptysis with diagnosis of pulmonary hydatid cyst. The incidence of hemoptysis in children may be as high as 38% as reported by Solak et al [5] In our child, echinococcal cyst could have initially caused obstruction to branch bronchi leading to stasis and infection. Later erosion of branch bronchi and peripheral pulmonary artery might have resulted in massive hemoptysis.…”
Section: Discussionsupporting
confidence: 59%
“…Singh S et al, [4] have reported a 10-year-old child with recurrent hemoptysis and a bout of massive hemoptysis with diagnosis of pulmonary hydatid cyst. The incidence of hemoptysis in children may be as high as 38% as reported by Solak et al [5] In our child, echinococcal cyst could have initially caused obstruction to branch bronchi leading to stasis and infection. Later erosion of branch bronchi and peripheral pulmonary artery might have resulted in massive hemoptysis.…”
Section: Discussionsupporting
confidence: 59%
“…7 There are many published reports about hydatid disease in adults, but there are few in the pediatric age group. 9 We report our experience in 376 pediatric cases with hydatidosis.…”
Section: Introductionmentioning
confidence: 98%
“…Literatürde %0-11 arasında nüks oranları bildirilmiştir. [5,21] Bizim çalışmamızda dört hastada akciğerde nüks gelişti. Takiplerde yakalanan nüks hastalarının dördüne tekrar torakotomi ile kistotomi kapitonaj uygulandı.…”
Section: Discussionunclassified